Impact of Climate and Rapid Land Use Changes on Runoff Quantities in Lower-Lampao River Basin: doi: 10.14456/mijet.2016.7 - Prasanchum, Haris; Kangrang, Anongrit; Hormwichian, Rattana; Compliew, Sudarat (Engineering Access, 2016)
Climate change which is the trend of rising temperatures or rainfall increased, rapid land use change from forest to agriculture and urban areas, are reasons for the changes in runoff cause to flooding and drought in many areas. Predicting future climate and land use can contribute to the planning, development and management of water in the basin proper. The objective of this study aims to examine the impact of climate and land use changes on runoff quantities in the Lower-Lampao River Basin, which is a sub-basin in the Chi River Basin, Northeast of Thailand. The procedure comprises: 1) climate change scenario by using PRECIS model; 2) land use change and runoff quantities analysis by using SWAT model. Climate simulations showed an average rainfall increased to 14.5 mm, average daily temperature with maximum increase to 2.6 degrees Celsius and minimum increase to 1.8 degrees Celsius. The runoff simulation shows the land use change from paddy fields to crops and urban area from 20, 40, 60, 80 and 100 percent increased. The amount of the average annual runoff is lower than the baseline year average runoff is between 16.6 to 35 percent, with the exception of the years 2012-2021, the average runoff higher than baseline year 13.4 percent. In conclusion, climate and land use changes have a direct impact on the amount of runoff decrease. The methodology and results of this study can be applied to analyze the runoff in other watershed areas with topography and hydrological conditions similar to this study area.